Konseptualisasi Model Manajemen Layanan Bimbingan dan Konseling Berbasis Website di Sekolah - Lakadjo, Mohamad Awal; Dwinanto, Arif; Pautina, Mohamad Rizal; Siregar, Ilham Kahiri (ILIN Education Indonesia, 2025)
School counseling services in Indonesia continue to face challenges, including fragmented management, weak evaluation systems, and limited technology integration. This study aims to develop a conceptual model for a web-based management system for school counseling services that is integrated, evidence-based, and adaptive to the Indonesian educational context. The study employed a Comprehensive Literature Review (CLR) approach with thematic analysis of national and international literature. The findings identified eight major challenges in school counseling services, the need for a digital management system based on data and aligned with national regulations, and resulted in a framework consisting of five integrated service cycles. Scientifically, this research expands the theoretical development of web-based counseling service management systems with a contextualized local approach. Practically, the model provides a concrete solution to enhance the effectiveness, accountability, and sustainability of school counseling services in Indonesia, while accelerating the adoption of evidence-based practices in educational settings.